Bacteroides fragilis Acute Hematogenous Osteomyelitis in a Young Female with Sickle Cell Disease - Nada Bassam Hamieh; Hiba Abdul Hamid Abou Layla; Rola Ali Ali; Zeina Bayram; Abdul Rahman Bizri (Case Reports in Infectious Diseases)
Patients with sickle cell disease are at increased risk for multiple infections including osteomyelitis. The most reported causative organisms are Salmonella spp. and Staphylococcus aureus. Anaerobic infections including Bacteroides fragilis are not commonly seen. Here, we report the first case of a 28-year-old female patient with sickle cell disease and acute hematogenous Bacteroides fragilis tibial osteomyelitis. Diagnosis was made by isolating the organism from blood and tibial fluid cultures. The patient was successfully managed with a course of intravenous followed by oral antibiotics and percutaneous drainage of collection and responded well. This case report will shed light on the importance of Bacteroides fragilis as a causative organism for osteomyelitis in sickle cell disease patients, thereby affecting the management of these patients.